Plasticity theory - Lubliner, Jacob (Dover books on engineering., 2008)
This self-contained text for advanced undergraduate and graduate students is devoted to classical quasistatic problems of rate-independent plasticity theory. It discusses the finite element method for both viscoplastic and rate-independent plastic solids, in addition to large deformation plasticity numerical methods for rate-based formulations and hyperelastic methods. 1990 edition.